VITOR MARINHO DE OLIVEIRA: A DIP IN THE THOUGHT OF TRAINING PHYSICAL EDUCATION BRAZILIAN (Fiep Bulletin - online, 2013)
This research and a cut of the work developed in a partnership between the Memory Center, Information and Documentation of the sport, Physical Education and Leisure - CEMIDEFEL and the Research Group on Social Representations and imagination on the Physical Education – you direct avant, which presents a goal to rescue, organize, preserve and make available the memory of Physical Education in relevant fields to school, different training methods, dance, sports and leisure. To achieve our goal we use principles of theoretical-methodological of Oral History, associated with the survey of information on the social actor involved with the research collected in written sources, iconographic, she publishes articles and life history. This study can be characterized with a deep diving in memory and in pedagogical thinking of one of the most relevant, significant and influential contemporary thinkers of Physical Education, the educator, researcher and historian Professor Vitor Marine de Oliveira. To develop we consider the relevance of oral evidence, since it is emerging from the information on the event. To develop we consider the relevance of oral evidence, since it is emerging from the information on the event. For both, we are registering the ransom from the memory of social actor through interviews and recorded statements, which are being transcribed, and filmed, concomitant to the development of a process of reading radical and critical of their three main academic books - What is Physical Education, Physical Education and humanist consensus and Conflict: Physical Education. The interview is being conducted from themes, previously agreed with the actor, and that address their involvement with events that are directly or indirectly, can be seen as conditions determining the understanding of the pedagogical thinking he produced.
Keywords: Physical Education. Oral History; Memory; Thought Pedagogigo